The development of ultrasensitive microcalorimeters for bioanalysis and energy balance monitoring - Hanliang Zhu; Lan Wang; Jianguo Feng; Pavel Neuzil (Fundamental Research)
Heat generation or consumption is required for all biological processes. Microcalorimetry is an ultrasensitive method to measure heat change for various applications. In this paper, we aimed to review the ultrasensitive microcalorimeter systems and their extensive applications in bioanalysis and energy balance monitoring. We first discussed the basic structure of microcalorimeters, including the closed system and open system, temperature sensing methods, isolation materials, and temperature stabilization. Then, we focused on their applications, such as cell metabolism research, biomolecule interaction measurement, biothermal analysis, and calorimetric detection. Finally, we compared the advantages and disadvantages of commercially available microcalorimeters and their contributions to bioresearch. The development of ultrasensitive microcalorimeters provides the tools for bioanalysis at the single-cell, or even subcellular, level, as well as for precise calorimetric detection.